Factors shaping the content of informative statements: cases of members of secret societies (the thirties – seventies of the nineteenth century) - Kulecka, Alicja (Folia Toruniensia, 2021)
The purpose of these considerations was to show the factors influencing the content of the investigative statements, and thus their informative value depending mainly on the research goals. These included, among others, the circumstances of the arrest and interrogation, the treatment of the suspect, the way of conducting conversations, asking questions, exerting pressure, establishing a rough description of the reality. They also presented the leading forms and contents of the statements. Some attention was also paid to the attitudes of historians towards this type of sources. The analyses carried out showed that the contents of the statements were shaped by: a. information obtained by the investigators from other statements and other sources, b. news revealed by the interrogated, c. striving to protect one's own person by the interrogated, d. the investigators' desire to establish facts and impose a punishment. The result of these considerations is also the thesis that there is no pure form of statement, e.g. only restrained or only sincere. A statement, regardless of its content and form, should be considered an important source for examining the mentality of the nineteenth century, the information needs of administrative, police, and judicial authorities in individual political systems, especially in the circumstances of the crisis of social trust, the personality of members of secret organizations, internal relations in secret societies, social structures, ideas and imaginations of this period, the attitudes of the authorities towards the needs of the collective, and more broadly the relationship between the authorities and the society, and the authorities and an individual.